2018
DOI: 10.1590/2177-6709.23.5.058-064.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mangosteen peel extract as an antioxidant agent on the shear bond strength of orthodontic brackets bonded to bleached teeth

Abstract: Introduction: The number of patients who seek orthodontic treatment that may have a history of tooth bleaching is increasing over the time. Bleaching may influence the decrease of the bond strength of orthodontic brackets. Objective: To determine and prove the effect of mangosteen peel (MP) extract to reverse the reduced shear bond strength (SBS) of orthodontic brackets after bleaching. Methods: A total of 150 maxillary first premolar teeth were randomly divided into 6 experimental groups as follow (n=25): neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Pine bark extract stands out among the PACs evaluated (81,82). While cranberry and gooseberry extracts were not satisfactory for the recovery of bond strength (75,83), mangosteen extract and quercetin compound seem promising (84,85) and should be compared to pine bark in further studies in order to confirm the superiority of the pine bark extract among the PACs.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pine bark extract stands out among the PACs evaluated (81,82). While cranberry and gooseberry extracts were not satisfactory for the recovery of bond strength (75,83), mangosteen extract and quercetin compound seem promising (84,85) and should be compared to pine bark in further studies in order to confirm the superiority of the pine bark extract among the PACs.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…However, the type of PAC, preparation mode, or concentration seems to influence the results. For instance, while a gooseberry (amla‐ Phyllanthus embelicus ) solution was not as efficient as a 10% SA solution in recovering the bond strength of brackets bonded to human bleached enamel (83), the opposite was observed for a mangosteen peel extract (84). A preliminary study showed that 0.1%, 0.5%, and 1.0% quercetin, a flavonoid found in many vegetables and seeds, may be another option for the recovery of the bleached enamel bond strength.…”
Section: Proanthocyanidinsmentioning
confidence: 99%
“…This adverse effect is naturally reversed in a period varying from 24 h to 3 weeks, 6 and a minimum delay of 7 days has been suggested before performing any adhesive procedure 7 . Nonetheless, such delay may result clinically inconvenient since patients frequently require restorative treatments after bleaching 8 as well as bracket cementation 9 …”
Section: Introductionmentioning
confidence: 99%
“…Today's society is witnessing an increased interest in cosmetic dentistry, thereby making orthodontics a necessity 1 . Orthodontic treatment has become one of the most procedures in cosmetic dentistry; it is performed to improve malocclusion, achieve good occlusion and dentofacial harmony 2, 3 .…”
Section: Introductionmentioning
confidence: 99%